2022
DOI: 10.1136/bmjopen-2021-057573
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional survey of education on LGBT content in medical schools in Japan

Abstract: ObjectivesWe aimed to clarify current teaching on lesbian, gay, bisexual, transgender (LGBT) content in Japanese medical schools and compare it with data from the USA and Canada reported in 2011 and Australia and New Zealand reported in 2017.DesignCross-sectional study.SettingEighty-two medical schools in Japan.ParticipantsThe deans and/or relevant faculty members of the medical schools in Japan.Primary outcome measureHours dedicated to teaching LGBT content in each medical school.ResultsIn total, 60 schools (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Education on LGBT issues is lacking within the USA, but the deficiency is even more conspicuous in Japan. A recent study reported that the proportion of medical schools that did not teach LGBT content at all during clinical training was significantly higher in Japan than in the USA and Canada (47.2% vs 33.3%) [8]. Other recent studies have found that over 90% of hospitals in Japan do not provide nursing training with LGBT content, despite the demand for this education [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Education on LGBT issues is lacking within the USA, but the deficiency is even more conspicuous in Japan. A recent study reported that the proportion of medical schools that did not teach LGBT content at all during clinical training was significantly higher in Japan than in the USA and Canada (47.2% vs 33.3%) [8]. Other recent studies have found that over 90% of hospitals in Japan do not provide nursing training with LGBT content, despite the demand for this education [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that, in Japan, the need for LGBT-related education has been demonstrated in medical and nursing education [24,28] and the current situation has been shown to be inadequate. [7,23] This survey focused on bioethics subjects in Japanese medical and nursing departments. Thirty percent of the respondents had already adopted this theme in their subjects, and a further 20% of respondents had an ambitious desire to adopt it in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The choices were knowledge, capability, ethical issues, coexistence, and dignity from several related studies. [7,24,25] The third, the author asked how much time was devoted to LGBT in the course. The fourth, the author asked them specifically about the content of LGBT education within the course.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations